2017
DOI: 10.1111/andr.12376
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa with numerical chromosomal abnormalities are more prone to be retained by Annexin V‐MACS columns

Abstract: Colloidal super-paramagnetic microbeads conjugated with annexin V are effective for separating apoptotic spermatozoa by MACS as a result of the high affinity of annexin V for externalized PS molecules. The effectiveness of the procedure in reducing the percentage of sperm with fragmented DNA and abnormal morphology has also been reported. However, it is still unknown if it could decrease the percentage of aneuploid spermatozoa. The objective of our prospective study, performed on 16 males with abnormal FISH on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(61 reference statements)
3
12
0
2
Order By: Relevance
“…Similar to these results, Zhang et al (2018) reported that the combination of DCG followed by AV-MACS in immotile sperm samples resulted in the recovery of a sperm population with lower DNA fragmentation compared to DGC alone. In agreement, Esbert et al (2017) reported that DGC followed by AV-MACS reduced the number of spermatozoa porting chromosomal abnormalities.…”
Section: Sperm Selection Based On Membrane Characteristicssupporting
confidence: 69%
“…Similar to these results, Zhang et al (2018) reported that the combination of DCG followed by AV-MACS in immotile sperm samples resulted in the recovery of a sperm population with lower DNA fragmentation compared to DGC alone. In agreement, Esbert et al (2017) reported that DGC followed by AV-MACS reduced the number of spermatozoa porting chromosomal abnormalities.…”
Section: Sperm Selection Based On Membrane Characteristicssupporting
confidence: 69%
“…These studies reported that processing samples through MACS decreased sperm aneuploidy rates in the annexin V (-) fraction. Moreover they compared the aneuploidy rate in the annexin V (-) and V (+) fractions and concluded that aneuploid sperm cells are preferentially retained in the MACS column (Esbert et al 2017). Our study is the first of its kind to evaluate the rate of normal or balanced spermatozoa and unbalanced spermatozoa after MACS in the two fractions of annexin V (-) and annexin V (+) for patients carrying a constitutional structural chromosomal abnormality.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, only two studies have worked on the effects of MACS on sperm aneuploidy rate in patients with a normal karyotype (Vendrell et al 2014;Esbert et al 2017). These studies reported that processing samples through MACS decreased sperm aneuploidy rates in the annexin V (-) fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Colloidal microbeads conjugated with annexin V effectively separated spermatozoa with numerical chromosomal aberrations and apoptotic spermatozoa (Esbert et al, 2017) and this procedure can be applied to select spermatozoa needed for the ICSI procedure. Colloidal microbeads conjugated with annexin V effectively separated spermatozoa with numerical chromosomal aberrations and apoptotic spermatozoa (Esbert et al, 2017) and this procedure can be applied to select spermatozoa needed for the ICSI procedure.…”
Section: Apoptosis and Testicular Cadmium Levelmentioning
confidence: 99%
“…In men with varicocele, elevated levels of apoptosis were found in spermatozoa. Colloidal microbeads conjugated with annexin V effectively separated spermatozoa with numerical chromosomal aberrations and apoptotic spermatozoa (Esbert et al, 2017) and this procedure can be applied to select spermatozoa needed for the ICSI procedure.…”
Section: Apoptosis and Testicular Cadmium Levelmentioning
confidence: 99%